Chemical applications of the Laplacian spectrum. VI On the largest Laplacian eigenvalue of alkanes - Gutman Ivan; Vidović Dušica; Stevanović Dragan P. (Journal of the Serbian Chemical Society, 2002)
The largest Lapacian eigenvalue µ1 of the molecular graph is a quantity important in the theory of the photoelectron spectra of saturated hydrocarbons. It is shown that in the case of alkanes, the presence or absence of quaternary carbon atoms is the main structural feature on which µ1 depends. Within sets of all alkanes with a given number of carbon atoms the species (with and without quaternary carbons atoms) whose µ1-values are minimal and maximal are determined.